Structure-activity-relationship study of semi-synthetically modified fusicoccins on their stabilization effect for 14-3-3-phospholigand interactions. (1st November 2022) - Ogino, Nanami; Masuda, Ryoma; Lynn Punzalan, Louvy; Yamashita, Emi; Igaue, Shota; Inoue, Yoshihisa; Ohkanda, Junko
Graphical abstract: Abstract: The diterpene glucoside fusicoccin-A (FC-A) is a fungal phytotoxin that stabilizes the interaction of plant 14-3-3 protein and plasma membrane H + -ATPase by forming a stable ternary complex. Previous studies demonstrated that structurally modified FC-A derivatives exhibit significant antitumor activities but their synthesis involves an explosive reagent, limiting their utility and opportunities for further structure–activity-relationship studies. In this study, we synthesized a series of FC derivatives by introducing various substituents on the fusicoccan scaffold and on the glucoside moiety, and evaluated their stabilization effects on the binding of 14-3-3 to fluorescently labeled mode-1 and mode-3 phosphopeptides. The results showed that introducing an amino group at the 6′-position of the glucoside moiety improves stabilization. Furthermore, cell-based evaluation demonstrated that 6′-amino benzyl 21b exhibits higher antiproliferative activity than previously developed FC agents.